Negative active material and preparation method thereof, negative pole piece and potassium ion battery

The negative electrode active material is prepared by acid purification and oxidation through acid purification and oxidation, and high-temperature sintering, which solves the problem of insufficient cycle stability and rate performance of the negative electrode material of potassium ion battery, and achieves higher capacity retention and cycle performance.

CN119660707APending Publication Date: 2025-03-21CRRC IND INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411696487.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The commercialization of potassium ion batteries faces the problems of poor cycle stability and poor rate performance, mainly due to the large ion radius of potassium ions, resulting in volume expansion and structural instability of the negative electrode material.

Method used

By mixing the high-sulfur coal after acid purification and decomposition, the high-sulfur coal oxide was formed and the negative electrode active material was obtained by high-temperature sintering. This method increases the micropore structure and active sites of the material, improves the storage and transport capacity of potassium ions, and reduces the risk of volume expansion.

Benefits of technology

It improves the capacity retention and circulation performance of the negative electrode material, improves the rate performance and circulation life of the potassium ion battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660707A_ABST
    Figure CN119660707A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode active material and a preparation method thereof, a negative electrode plate and a potassium ion battery, the preparation method of the negative electrode active material comprises the following steps: mixing high-sulfur coal subjected to acid purification and impurity removal with an oxidizing agent, and carrying out oxidation treatment to obtain oxidized high-sulfur coal; and sintering the oxidized high-sulfur coal at high temperature to obtain the negative electrode active material. The negative electrode active material has a large number of microporous structures and rich active groups, storage sites of potassium ions are increased, the negative electrode structure is stabilized, the negative electrode capacity is improved, and then the capacity retention ratio and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potassium ion batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode plate and a potassium ion battery. Background Art

[0002] Potassium-ion batteries have been successfully applied in portable electronic devices and electric vehicles. However, the scarcity of lithium resources severely limits its application in large-scale energy storage. Potassium-ion batteries (PIBs) are considered to be the most promising alternative to LIBs because of their many potential advantages: (1) the abundance and low cost of potassium metal resources. (2) K / K + The standard redox potential of the battery (±2.92V vs. SHE) and Li / Li + The standard redox potentials of the batteries (±3.04 V vs. SHE) are comparable, indicating that PIBs have higher battery voltages. (3) The conductivity of the electrolyte in potassium ion batteries is higher than that in potassium ion batteries.

[0003] Despite this, the commercialization of potassium-ion batteries still faces the problems of poor cycle stability and poor rate performance. This is because the ionic radius of potassium is much larger than that of lithium. Using natural graphite as the negative electrode material for potassium-ion batteries, it shows a current density of 279 mA h g -1 However, at higher current densities, its capacity drops sharply, and at 1 A g -1 At a current density of only 50 mA hg -1 . At the same time, the cycle performance of graphite as a negative electrode material is poor, and its capacity retention rate is only 50% after 50 cycles. The poor rate performance and cycle stability may be related to the large ionic radius of K, which leads to the volume expansion of graphite. In order to solve this problem, many attempts have been made, but most of them have problems with cumbersome synthesis processes and high raw material costs, which greatly increases the difficulty of commercialization of PIBs. Therefore, high-performance, low-cost negative electrode materials for PIBs are urgently needed. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a negative electrode active material and a preparation method thereof, a negative electrode sheet and a potassium ion battery.

[0005] In a first aspect of the present invention, the present invention provides a method for preparing a negative electrode active material, the method comprising: The high-sulfur coal after acid purification and impurity removal is mixed with an oxidant for oxidation treatment to obtain oxidized high-sulfur coal; The oxidized high-sulfur coal is sintered at high temperature to obtain the negative electrode active material.

[0006] According to the preparation method of the negative electrode active material of the present invention, the high-sulfur coal after acid purification and impurity removal is mixed with an oxidant for oxidation treatment. The high-sulfur coal is oxidized by the oxidant, which can produce a large number of microporous structures on the surface of the high-sulfur coal, increase the potassium ion storage sites, and at the same time, the oxidation treatment can change the surface groups of the high-sulfur coal. Therefore, the negative electrode material obtained after high-temperature sintering of the oxidized high-sulfur coal has more active sites, which is more conducive to the embedding and extraction of potassium ions, and has better expansion inhibition and stability. At the same time, the residual S and N in the high-sulfur coal realize in-situ self-doping, improve the carbon layer distance, and increase the transmission rate of potassium ions. In addition, the chaotic layer structure and surface pores of the high-sulfur coal can accommodate more K + , making it have a higher capacity retention rate at high current density. As a result, the negative electrode active material has a large number of microporous structures and rich active groups, which increases the storage sites of potassium ions, stabilizes the negative electrode structure, improves the negative electrode capacity, and thus improves the capacity retention rate and cycle performance of the battery.

[0007] In some embodiments of the present invention, the acid purification and impurity removal comprises: treating the high-sulfur coal powder obtained by passing through a 100-300 mesh sieve with concentrated hydrochloric acid, and then treating it with a mixture of hydrofluoric acid and concentrated hydrochloric acid after drying. Impurities such as pyrite and ash introduced during the mining process can be effectively removed by acid purification and impurity removal.

[0008] Specifically, high-sulfur coal powder is obtained after passing through a 200-mesh sieve, the powder is placed in a polytetrafluoroethylene beaker, concentrated hydrochloric acid is added, and the solid (g) to liquid (ml) ratio is (0.5~1): (4~5), and the powder is stirred in a 60℃~80℃ water bath for 5h~7h. After being rinsed with a large amount of deionized water, the powder is filtered and dried to obtain a roughly purified high-sulfur coal powder. Subsequently, the roughly purified powder is placed in a polytetrafluoroethylene beaker again, and hydrofluoric acid and hydrochloric acid are added in a volume ratio of 1:1 and a solid-liquid ratio of (0.5~1.5): (4~6). The powder is stirred in a 60℃~80℃ water bath for 20h~30h. Finally, the powder is rinsed with a large amount of deionized water until neutral, and the powder is filtered and dried to obtain the purified high-sulfur coal powder.

[0009] According to the method for preparing the negative electrode active material of the present invention, the oxidant includes hydrogen peroxide, potassium permanganate solution, potassium dichromate solution or sodium hypochlorite solution, preferably hydrogen peroxide.

[0010] Furthermore, the concentration of hydrogen peroxide is 30% to 50%, the concentration of potassium permanganate solution is ..95% to 99%, the concentration of potassium dichromate solution is .99.5% to 99.8%, and the concentration of sodium hypochlorite solution is .6% to 14%.

[0011] In some embodiments of the present invention, the mass of the high-sulfur coal is Ag, the volume of the oxidant is B ml, and A:B is 1:(3~7).

[0012] In some embodiments of the present invention, the mixing time is 3h~10h. Further mixing and stirring is performed, for example, the mixing time is 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., or the range between any two of the above values. By controlling the mixing time within the above range, the surface of the high-sulfur coal can be fully oxidized, providing sufficient microporous structure and active groups, improving the potassium ion storage capacity of the negative electrode active material, and improving the structural stability of the negative electrode material. Specifically, the mixing can be at room temperature.

[0013] In some embodiments of the present invention, the high temperature sintering temperature is 700°C to 900°C, and the time is 2h to 3h. For example, the high temperature sintering temperature is 700°C, 800°C, 900°C, etc., or the range between any two of the above values; the time is 2h, 2.5h, 3h, etc., or the range between any two of the above values.

[0014] In some embodiments of the present invention, the sulfur content in the high-sulfur coal is 1wt%~2.5wt%. When the sulfur content in the high-sulfur coal is within the above range, the potassium ion transfer rate of the negative electrode material can be increased, thereby increasing the negative electrode capacity.

[0015] In some embodiments of the present invention, the N content in the high-sulfur coal is 1wt%~2.5wt%. When the N content in the high-sulfur coal is within the above range, the potassium ion transfer rate of the negative electrode material can be increased, thereby increasing the negative electrode capacity.

[0016] The method for preparing the negative electrode active material according to the present invention further comprises: The spherical graphite tails and the oxidant are mixed and oxidized to obtain oxidized spherical graphite tails, and the oxidized spherical graphite tails and the oxidized high-sulfur coal are mixed and sintered at high temperature to obtain negative electrode active materials.

[0017] By oxidizing the spherical graphite tailings, the types and quantities of oxygen-containing functional groups on the surface of the spherical graphite tailings can be increased. During the pyrolysis process, the active functional groups can produce cross-linking reactions with high-sulfur coal to increase the interface stability between the two, thereby constructing high-rate and long-cycle negative electrode materials.

[0018] It should be noted that, from a process perspective, spherical graphite tailings refer to the remaining part of natural graphite after spheroidization except for spherical graphite; in terms of shape, they are mainly in the form of flakes.

[0019] The principle of spheroidization of natural flake graphite is that the natural flake graphite particles undergo mechanical effects such as collision, shearing and friction in the spheroidizer, and the large flake particles undergo plastic deformation to form spherical and quasi-spherical particles, while the fine particles are adsorbed and closely attached to the main core, and spherical graphite is obtained after friction and de-angularization. Spheroidization can significantly improve the electrochemical properties of natural flake graphite. Spheroidized natural flake graphite materials have a smaller specific surface area and a higher tap density, thus having a higher first coulomb efficiency, a higher reversible specific capacity and better cycle stability. During the entire processing of natural graphite spheroidization, a lot of spheroidized micropowders (spherical graphite tailings) will be produced due to mechanical effects such as grinding and collision. At present, the spheroidized micropowder waste generated in the spheroidization process industry accounts for 50% to 60% of the total. This part of the waste is left after more than a dozen or even dozens of treatments. Spheroidized micropowders have low tap density, large specific surface area, and many surface defects. Therefore, this part of spheroidized micropowder can only be used to produce low-value-added lubricants and refractory materials, which greatly reduces the high-value utilization of natural flake graphite.

[0020] Therefore, the present invention adopts the above-mentioned spherical graphite tailings to not only improve the rate cycle performance of the negative electrode material, but also significantly improve the utilization rate of natural flake graphite spheroidized waste, effectively reduce the production cost, and has huge economic value.

[0021] In some embodiments of the present invention, the mass of the spherical graphite tail is M g, the volume of the oxidant is N ml, and M:N is 1:(3-7).

[0022] In some embodiments of the present invention, the spherical graphite tailings are oxidized for 3 hours to 10 hours.

[0023] Preferably, based on the total mass of the oxidized spherical graphite tailings and the oxidized high-sulfur coal, the mass proportion of the oxidized spherical graphite tailings is no more than 30%. For example, the mass proportion of the oxidized spherical graphite tailings is 30%, 25%, 20%, 15%, 10%, 5%, 1%, etc., or a range between any two of the above values. By controlling the addition amount of the oxidized spherical graphite tailings, the rate performance and cycle performance of the negative electrode active material can be significantly improved.

[0024] According to the method for preparing the negative electrode active material of the present invention, the negative electrode active material and a polyetheramine (PEA) solution modified by a silane coupling agent are mixed and stirred at room temperature, and then polyvinyl pyrrolidone is added to perform cross-linking polymerization.

[0025] The negative electrode active material and the polyetheramine solution modified by the silane coupling agent are mixed and stirred at room temperature, so that PEA can be grafted on the negative electrode active material. This is mainly because the spherical graphite tailings and / or high-sulfur coal are oxidized by an oxidant and have a large number of active groups on the surface, so the grafting of PEA can be achieved. Then, polyvinyl pyrrolidone (PVP) is added to the above-mentioned PEA-grafted negative electrode active material system. Polyvinyl pyrrolidone and PEA undergo a cross-linking reaction to form a PEA-PVP film layer on the surface of the negative electrode active material. This artificial SEI film formed on the surface of the negative electrode active material can improve the rate performance of the negative electrode material while enhancing the cycle life of the negative electrode.

[0026] Those skilled in the art will appreciate that the above-mentioned negative electrode active material can be either a negative electrode active material formed by sintering oxidized high-sulfur coal or a negative electrode active material formed by sintering a mixture of oxidized spherical graphite tailings and oxidized high-sulfur coal. Preferably, the negative electrode active material is a negative electrode active material formed by sintering a mixture of oxidized spherical graphite tailings and oxidized high-sulfur coal.

[0027] In some embodiments of the present invention, the preparation process of the silane coupling agent modified polyetheramine solution is: mixing a 4-5wt% alcohol solution of polyetheramine and an equal molar amount of a silane coupling agent solution, and stirring the mixture at 50°C-70°C for 10h-12h.

[0028] Preferably, the silane coupling agent is selected from KH560, which contains -NH2 and -OCH3, and these two functional groups react with -OH and -COOH in the negative electrode material to undergo dehydration reaction.

[0029] Furthermore, the polyetheramine solution modified by the silane coupling agent obtained above and the aqueous solution of the negative electrode active material (the concentration of the negative electrode active material is 2-4 mg / mL) are mixed and stirred.

[0030] In some embodiments of the present invention, the cross-linking polymerization temperature is 60°C to 70°C, and the time is 5h to 7h. By controlling the temperature and time of the cross-linking reaction within the above range, polyvinyl pyrrolidone and PEA can fully undergo cross-linking reaction to form a SEI film that completely covers the negative electrode active material.

[0031] Furthermore, an excess amount of polyvinyl pyrrolidone is added, and after the polymerization reaction is completed, the mixed solution is dialyzed and then freeze-dried to obtain a negative electrode active material coated with a SEI film.

[0032] In a second aspect of the present invention, a negative electrode active material is provided, and the negative electrode active material is prepared by the above method, so that the negative electrode active material has excellent capacity and stability.

[0033] In a third aspect of the present invention, a negative electrode sheet is provided, wherein the negative electrode sheet comprises the above-mentioned negative electrode active material, so that the negative electrode sheet has good stability, and a battery prepared by using the negative electrode sheet has excellent rate and cycle performance.

[0034] In some embodiments of the present invention, the negative electrode plate further includes a binder and a conductive agent.

[0035] As examples, the binder includes polyvinylidene fluoride, carboxylated polyvinylidene fluoride, modified SBR rubber, modified fluorinated rubber, modified polyurethane, and the like.

[0036] As examples, the conductive agent includes carbon black, carbon nanotubes, graphene, and the like.

[0037] In some embodiments of the present invention, the preparation process of the negative electrode plate includes: stirring and mixing the negative electrode active material, conductive agent, binder, and solvent to obtain a mixed slurry, and then evenly coating the mixed slurry on an aluminum foil and vacuum drying the mixed slurry to obtain a negative electrode plate.

[0038] In a fourth aspect of the present invention, a potassium ion battery is provided, wherein the battery comprises the above-mentioned negative electrode plate, thereby the battery has a higher rate performance and cycle life.

[0039] In some embodiments of the present invention, the lithium-sulfur battery further includes a positive electrode sheet and a battery separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 are SEM images of the negative electrode active materials of Example 1 of the present invention and Comparative Example 1; Figure 2 TEM images of the negative electrode active materials of Examples 1-2 and Comparative Example 1 of the present invention; Figure 3 is a TEM image of the negative electrode active material of Examples 3 and 4 of the present invention; Figure 4 are SEM and EDS images of the negative electrode active material of Example 3 of the present invention; Figure 5 is a graph showing the rate performance test results of negative electrode active materials of Examples 1-2 and Comparative Examples 1-2 of the present invention; Figure 6This is a graph showing the first coulombic efficiency test of the batteries of Examples 1-2 and Comparative Examples 1-2 of the present invention; Figure 7 1 is a graph showing the battery cycle performance test results of Examples 1-2 and Comparative Examples 1-2 of the present invention; Figure 8 1 is a graph showing the battery cycle performance test results of Example 2, Example 3 and Comparative Example 1 of the present invention; Fig. 9 It is the first coulombic efficiency diagram of the battery of Example 2 and Example 3 of the present invention; Fig.10 It is the surface morphology of the negative electrode active material after the battery cycle of Example 2 and Example 3 of the present invention. DETAILED DESCRIPTION

[0042] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0043] Example 1 The preparation process of the negative electrode active material of this embodiment is as follows: (1) Acid purification and impurity removal: After crushing the high-sulfur coal with a crusher, pass it through a 200-mesh sieve to obtain high-sulfur coal powder. Put the powder into a polytetrafluoroethylene beaker, add concentrated hydrochloric acid at a solid-liquid ratio of 1:5, stir it in a 70°C water bath for 6 h, rinse it with a large amount of deionized water, filter it and dry it to obtain roughly purified high-sulfur coal powder. Then put the roughly purified powder into a polytetrafluoroethylene beaker again, add hydrofluoric acid and hydrochloric acid at a volume ratio of 1:1 and a solid-liquid ratio of 1:5, stir it in a 70°C water bath for 24 h, and finally rinse it with a large amount of deionized water until it is neutral. Filter it and dry it to obtain purified high-sulfur coal powder. The sulfur content of the obtained high-sulfur coal powder is 1.585wt%, and the nitrogen content is 1.34wt%.

[0044] (2) The high-sulfur coal obtained in step (1) is placed in hydrogen peroxide with a solid-liquid ratio of 1:5, and reacted for 4 h under magnetic stirring. After filtration and drying, oxidized high-sulfur coal is obtained. The oxidized high-sulfur coal is placed in a muffle furnace filled with nitrogen for high-temperature carbonization. The carbonization temperature is 800°C, the heating rate is 7°C / min, and the insulation time is 2.5 h. After the muffle furnace is cooled to room temperature, the sample is taken out and recorded as OGLM.

[0045] Example 2 The preparation process of the negative electrode active material of this embodiment is as follows: (1) Step (1) of Example 2 is the same as that of Example 1.

[0046] (2) The graphite spherical tailings were placed in hydrogen peroxide with a solid-liquid ratio of 1:5, reacted under magnetic stirring for 4 hours, and filtered and dried to obtain oxidized graphite spherical tailings. The oxidized high-sulfur coal prepared in step (2) of Example 1 was mixed with the above-mentioned oxidized graphite spherical tailings, wherein the mass ratio of the oxidized high-sulfur coal to the oxidized graphite spherical tailings was 9:1, and the two were ground evenly using a mortar, and placed in a muffle furnace filled with nitrogen for high-temperature carbonization, the carbonization temperature was 800°C, the heating rate was 7°C / min, the insulation time was 2.5 hours, and the sample was taken out after the muffle furnace was cooled to room temperature, and recorded as OSGD-90%OGLM.

[0047] Example 3 The preparation process of the negative electrode active material of this embodiment is as follows: (1) To a 4 wt % polyetheramine PEA methanol solution, an equal molar amount of a silane coupling agent KH560 solution was added, and the mixture was stirred at 60° C. under a magnetic stirrer for 11 h to obtain a KH560-modified PEA methanol solution.

[0048] (2) A mixed solution of the negative electrode material OSGD-90% OGLM obtained in Example 2 and water (concentration of 3 mg / mL) was added to the above-mentioned KH560-modified PEA methanol solution, and magnetic stirring was performed at room temperature for 11 h to obtain a PEA grafted negative electrode material.

[0049] (3) Add an excess amount of polyvinyl pyrrolidone (PVP) reagent to the above-mentioned PEA grafted negative electrode material mixed solution, stir in a magnetic stirrer at 60°C for 6 h, dialyze the mixed solution, and freeze-dry to obtain a PEA / PVP cross-linked polymer grafted ball tail / hard carbon composite material, which is recorded as OSGD-90%OGLM-PEA-PVP.

[0050] Example 4 The preparation process of the negative electrode active material of this embodiment is as follows: (1) Step (1) of Example 4 is the same as step (1) of Example 3.

[0051] (2) A mixed solution of the negative electrode material OGLM obtained in Example 1 and water (concentration of 3 mg / mL) was added to the above-mentioned PEA methanol solution modified by KH560, and magnetic stirring was performed at room temperature for 11 h to obtain a PEA grafted negative electrode material.

[0052] (3) Add an excess amount of polyvinyl pyrrolidone (PVP) reagent to the above-mentioned PEA grafted negative electrode material mixed solution, stir in a magnetic stirrer at 60°C for 6 h, dialyze the mixed solution, and freeze-dry to obtain a PEA / PVP cross-linked polymer grafted ball tail / hard carbon composite material, which is recorded as OGLM-PEA-PVP.

[0053] Comparative Example 1 The preparation process of the negative electrode active material of this comparative example is as follows: The graphite spherical tailings were placed in hydrogen peroxide with a solid-liquid ratio of 1:5, reacted under magnetic stirring for 4 h, and filtered and dried to obtain oxidized graphite spherical tailings. The oxidized graphite spherical tailings were placed in a muffle furnace filled with nitrogen for high-temperature carbonization at a carbonization temperature of 800 ° C, a heating rate of 7 ° C / min, and a holding time of 2.5 h. After the muffle furnace was cooled to room temperature, the sample was taken out and recorded as OSGD.

[0054] Comparative Example 2 The preparation process of the negative electrode active material of this comparative example is as follows: (1) The step (1) of Comparative Example 2 is the same as the step (1) of Example 1.

[0055] (2) The high-sulfur coal powder obtained in step (1) is placed in a muffle furnace filled with nitrogen for high-temperature carbonization. The carbonization temperature is 800°C, the heating rate is 7°C / min, and the insulation time is 2.5 h. After the muffle furnace is cooled to room temperature, the sample is taken out and recorded as GLM.

[0056] The performance of the negative electrode active materials prepared in the examples and comparative examples was measured, as follows: (1) SEM images of the negative electrode active materials of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, from Figure 1 It can be seen that the surface morphology of OSGD shows that small-particle graphite agglomerates and the particle size distribution is uneven, which makes it difficult to embed potassium ions. In addition, large-sized potassium ions embedded in graphite will cause a large volume expansion, affecting its electrochemical performance.

[0057] (2) TEM images of the negative electrode active materials of Examples 1-2 and Comparative Example 1 are as follows: Figure 2 As shown, from Figure 2 It can be seen that OSGD presents a relatively regular layered structure with an interlayer spacing of about 0.335 nm. Large-sized potassium ions embedded in graphite flakes are prone to volume expansion, which affects the service life and rate performance of the negative electrode material. The structural characteristics of OGLM are consistent with the chaotic layer structure of typical hard carbon materials, and the crystal structure is isotropic, which is conducive to the embedding and extraction of K+, and can effectively alleviate the volume expansion problem of the negative electrode material, which is conducive to improving the rate performance of the negative electrode at high current density. The structural characteristics of OSGD-90%OGLM are a composite of layered structure and chaotic layer structure, and with the increase of OGLM content, the proportion of chaotic layer structure increases significantly. The composite material of the two does not affect the inherent structure of natural graphite and high-sulfur coal. Therefore, the composite material can significantly improve the rate performance and cycle life of the negative electrode due to the presence of high-sulfur coal. At the same time, the presence of natural graphite can alleviate the problem of low first coulomb efficiency caused by excessive specific surface area to a certain extent.

[0058] (3) TEM images of the negative electrode active materials of Examples 3 and 4 are shown in Figure 3 As shown, from Figure 3 It can be seen from the transmission electron microscope image of OGLM-PEA-PVP that PEA / PVP is coated on the surface of the ball tail with a thickness of about 20 nm, indicating that the polymer grafting reaction is successful. Through the surface morphology of OSGD-90%OGLM-PEA-PVP, it can be clearly observed that the coating layer of the composite material is uneven, which may be due to the inconsistent content of -COOH and -OH on the surface of the ball tail and high-sulfur coal, and the uneven mixing of graphite and hard carbon, resulting in uneven coating thickness.

[0059] (4) The SEM and EDS images of the negative electrode active material of Example 3 are as follows: Figure 4 As shown, from Figure 4 It can be seen that the composite material mainly contains five elements: C, O, S, N, and Si. The O element is attributed to the large number of oxygen-containing functional groups in the edges of graphite and high-sulfur coal and cross-linked polymers. The presence of S and N elements is due to the presence of high-sulfur coal. The presence of S and N elements in high-sulfur coal can achieve in-situ doping. More importantly, the presence of Si element was observed in the EDS energy spectrum. The main reason is that the PEA modified by KH560 is connected to graphite through C-Si bonds, proving that the grafting reaction was successful.

[0060] (5) The negative electrode active material, acetylene black and polyvinylidene fluoride (PVDF) were dissolved in N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:1, stirred at room temperature for 4 h, and the slurry was coated on aluminum foil to prepare a working electrode. It was then placed in a 45°C forced air drying oven for 1 h and then placed in a 110°C vacuum drying oven for 12 h. The working electrode and the counter electrode were separated using a Celgard-2400 separator. Potassium metal was used as the counter electrode, and 1 M KPF6 electrolyte was dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (1:1, v / v) as the electrolyte. CR2032 button batteries were made and charged and discharged using a blue battery system. The battery assembly process was carried out in an argon-filled glove box, and the water and oxygen contents in the glove box were both less than 0.1 ppm.

[0061] The rate performance and cycle performance are both tested on the Blue Dot system. By setting a special program, the button battery is charged and discharged. Rate performance test conditions: at a current density of 0.05Ag -1 , 0.1Ag -1 , 0.2Ag -1 , 0.5Ag -1 , 1.0Ag -1The cycle performance is tested at 0.1 Ag -1 Tested at current density.

[0062] The test results of the battery’s rate performance and cycle performance (200 cycles) are shown in Table 1.

[0063] Table 1

[0064] Combination Figure 5-9 As shown in Table 1, compared with Comparative Example 2, the negative electrode material prepared by oxidizing high-sulfur coal in Example 1 has higher rate performance, and the battery has excellent capacity retention rate and first coulombic efficiency. The negative electrode material of Example 2 is based on Example 1 and adds oxidized graphite spherical tailings. The rate performance, capacity retention rate and first coulombic efficiency of Example 2 are significantly improved. Example 3 is based on Example 2, and the surface of the negative electrode active material is coated with PEA / PVP film. The capacity retention rate and first coulombic efficiency of the battery are further improved. At the same time, combined with Fig.10 It can be seen that the PEA / PVP coating film effectively isolates the negative electrode from direct contact with the electrolyte. More importantly, compared with Example 2, the SEI surface fracture phenomenon after cycling in Example 3 is significantly weakened, indicating that the introduction of PEA / PVP cross-linked polymer significantly enhances the stability of SEI, thereby improving the cycle life of the material.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a negative electrode active material, characterized in that: include: The high-sulfur coal after acid purification and impurity removal is mixed with an oxidant for oxidation treatment to obtain oxidized high-sulfur coal; The oxidized high-sulfur coal is sintered at high temperature to obtain the negative electrode active material.

2. The method according to claim 1, characterized in that: The oxidant includes hydrogen peroxide, potassium permanganate solution, potassium dichromate solution or sodium hypochlorite solution, preferably hydrogen peroxide; And / or, the mass of the high-sulfur coal is Ag, the volume of the oxidant is B ml, and A:B is 1:(3-7); And / or, the mixing time is 3h~10h.

3. The method according to claim 1, characterized in that: The high temperature sintering temperature is 700° C. to 900° C., and the sintering time is 2 h to 3 h.

4. The method according to claim 1, characterized in that: The sulfur content of the high-sulfur coal is 1wt%~2.5wt%; And / or, the N content in the high-sulfur coal is 1wt%~2.5wt%.

5. The method according to any one of claim 1, characterized in that: Also includes: The spherical graphite tails are mixed with the oxidant to perform oxidation treatment to obtain oxidized spherical graphite tails, and the oxidized spherical graphite tails are mixed with the oxidized high-sulfur coal and then sintered at high temperature to obtain a negative electrode active material; Preferably, based on the total mass of the oxidized spherical graphite tailings and the oxidized high-sulfur coal, the mass proportion of the oxidized spherical graphite tailings is no more than 30%.

6. The method according to any one of claims 1 to 5, characterized in that: The negative electrode active material and the polyetheramine (PEA) solution modified by the silane coupling agent are mixed and stirred at room temperature, and then polyvinyl pyrrolidone is added to carry out cross-linking polymerization.

7. The method according to claim 6, characterized in that: The preparation process of the silane coupling agent modified polyetheramine solution is as follows: after mixing a polyetheramine alcohol solution with a concentration of 4-5wt% and an equal molar amount of a silane coupling agent solution, stirring at 50°C-70°C for 10h-12h, preferably, the silane coupling agent is selected from KH560; And / or, the cross-linking polymerization is carried out at a temperature of 60° C. to 70° C. and for a time of 5 h to 7 h.

8. A negative electrode active material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. A negative electrode plate, characterized in that: Comprising the negative electrode active material according to claim 8.

10. A potassium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Electrode material with cross-linked carbon-coating mesoporous silicon particles and preparation method thereof

    CN110289402A

  • Method for preparing high-rate lithium battery negative electrode material from natural graphite spherical tailings

    CN114864935A

  • Method for preparing high-rate lithium battery negative electrode material from natural graphite spherical tailings

    CN115799500A

  • Sulfur-carbon composite, positive electrode for lithium secondary battery including same, and lithium secondary battery

    EP3968408A1